IMPELEMENTASI NILAI-NILAI PANCASILA PADA SISWA KELAS X A SMA NEGERI 1 SUKASADA - Kondi, Marsel Marthen; Utami, Anak Agung Istri Dewi Adhi; Sidaryanti, Ni Nyoman Asri (Program Studi PPKn Universitas Pendidikan Ganesha, 2026)
This study aims to describe the implementation of Pancasila values ​​in class X A students at SMA Negeri 1 Sukasada, identify factors that hinder its implementation, and explain the solutions implemented by the school to overcome these obstacles. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects included the principal, Pancasila Education teachers, and class X A students. The results of the study indicate that Pancasila values ​​have been implemented through classroom learning activities, religious habits such as group prayer and Tri Sandya, social activities, extracurricular activities, and student organizations. The implementation of the five principles is reflected in students' religious attitudes, tolerance, cooperation, deliberation, and social responsibility. However, the implementation still faces obstacles, both internal factors such as low student motivation and limited character learning methods, as well as external factors such as the influence of social media and the family environment. To overcome these obstacles, the school has strengthened the curriculum, trained teachers, increased student participation, and collaborated with parents and the community. Overall, the implementation of Pancasila values ​​has gone quite well and contributed to the formation of student character.